Caracterización de las inteligencias múltiples y los estilos de aprendizaje en 7° y 8° grado de una institución pública del corregimiento Guacamayal, del municipio Zona Bananera. (2024)
The purpose of this study is to characterize multiple intelligences and learning styles in 7th and 8th grade students of a public institution in the Guacamayal district, in the Zona Bananera municipality. Therefore, relate the theoretical approaches that both models have, from some perspectives. This research becomes relevant by addressing the need to strengthen the teaching and learning processes, the different learning styles must be kept in mind for a better adaptation of the students, and they can better enhance their skills by acquiring information more easily. This research is Quantitative, meaning that the information collected is represented on numerical scales, comparison between groups and relationships between the variables. On the other hand, it is non-experimental in nature, since the study of the data from the educational institution was carried out without the intention of manipulating the variables obtained. In addition, it has a Descriptive level as its scope, where the aim is to identify the characteristics and other relevant elements. For this, Howard Gardner's multiple intelligences test was used, and Lynn O'Brien's test to identify the learning perception preference channel. Consequently, in the application, teachers must take into account activities and strategies that are visual and verbal skills in students, in order to favor the learning and teaching processes in the institution.